2016
DOI: 10.1111/nmo.12748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pacifier and taste on swallowing, esophageal motility, transit, and respiratory rhythm in human neonates

Abstract: Background Pacifier use is widely prevalent globally despite hygienic concerns and uncertain mechanistic effects on swallowing or airway safety. Aims The effects of pacifier and taste interventions on pharyngo-esophageal motility, bolus transit and respiratory rhythms were investigated by determining the upper esophageal sphincter (UES), esophageal body, esophagogastric junction (EGJ) motor patterns as well as deglutition apnea, respiratory rhythm disturbances and esophageal bolus clearance. Methods Fiftee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
(111 reference statements)
0
12
0
Order By: Relevance
“…The effects of neurologic, cardiorespiratory, and aerodigestive factors on regulation of biorhythms involved with feeding safety need further longitudinal study in premature infants with evolving disease, such as neuropathology or BPD. Such studies should incorporate patient-specific bedside tools, such as highresolution manometry studies [32][33][34][35] or NIRS 12,36 to assess the compensatory mechanisms. If infants with severe AOP showing decompensation features with oral feeding attempts, effects of interventions (use of Erythropoietin and Darbepoetin), which also have neuroprotective effects, on prevention of AOP and oral feeding outcomes could be tested in future studies or as a secondary outcome in ongoing randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of neurologic, cardiorespiratory, and aerodigestive factors on regulation of biorhythms involved with feeding safety need further longitudinal study in premature infants with evolving disease, such as neuropathology or BPD. Such studies should incorporate patient-specific bedside tools, such as highresolution manometry studies [32][33][34][35] or NIRS 12,36 to assess the compensatory mechanisms. If infants with severe AOP showing decompensation features with oral feeding attempts, effects of interventions (use of Erythropoietin and Darbepoetin), which also have neuroprotective effects, on prevention of AOP and oral feeding outcomes could be tested in future studies or as a secondary outcome in ongoing randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions with pacifiers have been shown to facilitate UES relaxation in swallowing and primary peristalsis by decreasing the cholinergic excitatory output to both the UES and lower esophageal sphincter via the vagus nerve. 15 The addition of taste intervention has also been shown to result in primary peristalsis rhythm sequences occurring more rapidly with rapid restoration of respiratory normalcy after completion of the primary peristalsis. 15 Both of our cases demonstrated an increase in primary peristalsis after providing them a fruit-based product.…”
Section: Discussionmentioning
confidence: 99%
“…15 The addition of taste intervention has also been shown to result in primary peristalsis rhythm sequences occurring more rapidly with rapid restoration of respiratory normalcy after completion of the primary peristalsis. 15 Both of our cases demonstrated an increase in primary peristalsis after providing them a fruit-based product.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that the oral, pharyngeal, and esophageal, phases of swallowing are independent of each other (2, 3), future work is needed to evaluate correlation of oromotor phases with pharyngeal and esophageal phases. Pharyngeal swallowing or UES contraction may be induced by oral, pharyngeal, esophageal, tussive, or gastroesophageal reflux stimuli (3, 5, 7, 17, 1923, 27, 4446). Thus, terminologies have been adopted to distinguish responses due to these specific testing conditions.…”
Section: Discussionmentioning
confidence: 99%